IMPLEMENTASI METODE EARNED VALUE DENGAN LIFE CYCLE COST (LCC) PADA PROYEK PEMBANGUNAN GEDUNG PENDIDIKAN - Ni Komang Sintyawati; Wayan Gde Erick Triswandana; Putu Aryastana (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Construction projects are a series of activities that are typically one-time and short-term. Ongoing projects often experience delays, both in terms of completion time exceeding the plan and implementation costs being higher than those projected in the Implementation Budget Plan (RAP). Deviations from the plan must be continuously measured to control costs and time. Ineffective project management is marked by significant deviations in costs and time. The purpose of this research is to evaluate the performance of the Warmadewa University Educational Building construction in terms of cost and time using the Earned Value Method, and to identify solutions to address delays. Additionally, to determine the economic value of a building based on its operational costs throughout its lifespan, Life Cycle Cost (LCC) is used in this study. This research employs a descriptive method with a quantitative approach, utilizing necessary data such as plan drawings, RAB, time schedules, and weekly reports. The performance analysis results show an SPI value of 0.81, indicating that the project is delayed from the planned schedule. Meanwhile, the CPI value is 1, meaning that the work is in line with the planned budget. If project performance remains stable until completion, the estimated total cost (EAC) will match the plan at IDR 23,948,882,427.62. The estimated project time (EAS) is longer than the initial plan, from 380 days to 428 days, indicating an extension of 48 days. Using LCC calculations for the Warmadewa University Educational Building project, the total maintenance cost for wall, floor, and ceiling work is IDR 19,403,342.58.